Teacher educators as curriculum developers: exploration of a professional role. Issue 1 (1st January 2018) - Bouckaert, Marina; Kools, Quinta
Abstract: Teacher educators arguably fulfil several roles in their professional context: they can be seen as role models or teachers of teachers, and have additionally been characterised as researchers, mentors, gatekeepers, brokers, and curriculum developers. To address a perceived gap in the literature on the latter role, a quantitative and qualitative exploratory study into educators' own perceptions of their role as curriculum developers was conducted at a large teacher education department in the Netherlands. Seventy-five educators completed a digital questionnaire. Their responses reveal that the participants generally consider themselves to be curriculum developers, are aware of the responsibilities this professional role entails, and can pinpoint concrete practices in which the role becomes visible. The findings furthermore suggest that educators have been prepared for and develop professionally in this role in a variety of ways, mostly through informal learning with their colleagues at the workplace. Based on these findings, recommendations are made to inform educational practice, policy, and research.